Neomycin resistance as a selectable marker in Methanococcus maripaludis. - Argyle, J L (1996)
We cloned the aminoglycoside phosphotransferase genes APH3'I and APH3'II between the Methanococcus voltae methyl reductase promoter and terminator in a plasmid containing a fragment of Methanococcus maripaludis chromosomal DNA. The resulting plasmids encoding neomycin resistance transformed M. maripaludis at frequencies similar to those observed for pKAS102 encoding puromycin resistance. The antibiotic geneticin was not inhibitory to M. maripaludis.